Employment protection reforms, employment and the incidence of temporary jobs in Europe: 1995 - 2001 - Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2007)
Using European Community Household Panel data for nine countries for 1996-2001, I investigate the impact of reforms of employment protection systems on employment and on temporary jobs for wage and salary workers. Individual fixed effects models are estimated, with the inclusion of country-specific trends in the dependent variable, addressing the possibly changing labor force composition and the possible endogeneity of the reforms. A basic finding that is robust to all specifications and to the disaggregation of the sample by country is that policies making it easier to create temporary jobs raise the likelihood that wage and salary workers will be in temporary jobs. However, there is no evidence that such reforms raise employment, and in some countries, they appear to lower employment. Thus, these reforms appear rather to encourage a substitution of temporary for permanent work. Reforms of permanent employment protection mandates have small and insignificant effects on employment and temporary jobs on average. Moreover, when I disaggregate by country, such reforms appear more often to lower overall employment and to lower the share of employment in permanent jobs. These are likely to reflect short run impacts of such reforms, which make it easier for firms to discharge substandard workers.
Keywords: J21; 330; Employment protection; temporary jobs; Arbeitnehmerschutz; Kündigungsschutz; Reform; Deregulierung; Wirkungsanalyse; Beschäftigungseffekt; Leiharbeit; Befristeter Arbeitsvertrag; EU-Staaten